Proprioception in Action: A Matter of Ecological and Social Interaction - González-Grandón, Ximena; Falcón-Cortés, Andrea; Ramos-Fernández, Gabriel (Frontiers in Psychology, 2021)
The aim of this paper is to provide a theoretical and formal framework to understand how the proprioceptive and kinaesthetic system learns about body position and possibilities for movement in ongoing action and interaction. Whereas most weak embodiment accounts of proprioception focus on positionalist descriptions or on its role as a source of parameters for internal motor control, we argue that these aspects are insufficient to understand how proprioception is integrated into an active organized system in continuous and dynamic interaction with the environment. Our strong embodiment thesis is that one of the main theoretical principles to understand proprioception, as perceptual experience within concrete situations, is the coupling with kinesthesia and the relational constitution ---self, ecological and social---. In our view, these aspects are underdeveloped in current accounts, and an enactive sensorimotor theory enriched with phenomenological descriptions of experience may provide an alternative path towards explaining this skilled experience. Following \citet{oregan01} sensorimotor contingencies conceptualization, we introduce three distinct notions of proprioceptive kinaesthetic-sensorimotor contingencies (PK-SMCs), which we describe conceptually and formally considering three varieties of perceptual experience in action: PK-SMCs-self, PK-SMCs-self-environment, and PK- SMC self-other. As a proof of concept of our proposal, we develop a minimal PK model to discuss these elements in detail and show their explanatory value as important guides to understand the proprioceptive/kinaesthetic system. Finally, we also highlight that there is an opportunity to develop enactive sensorimotor theory into new directions, bridging between the varieties of experience of oneself and learning skills